Sustainable Development in the Light of the Teachings of the Encyclical Laudato Si - Alva, Reginald (European Journal of Sustainable Development, 2016)
Pope Francis’ encyclical Laudato Si is a part of the Church’s Magisterium. However, it contains deep insights, which encourage sustainable development of our planet. It includes everyone and everything, as all are inter-related. The contemporary world does not lack scientific studies on the problems of the earth. However, scientific studies are not sufficient to find concrete solutions to the problems, which humanity is facing. Even though, the encyclical does not claim to be a scientific document on ecology, it raises our attention to look into the problems of our planet and resolve to deal with them holistically. In this paper, we shall examine the suggestions in the encyclical Laudato Si, which call upon the whole humanity to come together to work towards sustainable development of our planet. We shall compare the scientific concept of sustainable development with Pope Francis’ understanding of the same term. Our sources for study will be the encyclical, other documents of the Church on similar subject and opinions of experts in this field. Keywords: Laudato Si, Sustainable development, social dimension, ethical standards.